2023
DOI: 10.1029/2022gl102263
|View full text |Cite
|
Sign up to set email alerts
|

Do the Throat Auroras Create Polar Cap Patches?

Abstract: Throat auroras and polar cap patches are common phenomena in the polar ionosphere resulting from solar wind-magnetosphere-ionosphere coupling. The throat aurora is a discrete aurora that is associated with localized magnetopause indentations (Han, 2019). It is usually located equatorward of the cusp aurora oval near magnetic noon, oriented in the south-north direction (Han et al., 2015) and is more frequently observed under radial interplanetary magnetic field (IMF, Bx-dominated conditions) (e.g., Han et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…There were also several auroral arcs on the nightside from 1404 UT observed by the RSB ASI at 630.0 nm band. Previous studies have suggested that polar cap patches are related to dayside auroral structures like poleward moving auroral form (PMAF) (Lorentzen et al., 2010; Nishimura et al., 2014; Zhang et al., 2010) and throat aurora (Zhang et al., 2023). Our auroral arc was accompanied by electron density enhancement and soft‐electron precipitation (Michell et al., 2008), but the relationships between polar cap patches and auroral arcs in the polar cap needs to be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also several auroral arcs on the nightside from 1404 UT observed by the RSB ASI at 630.0 nm band. Previous studies have suggested that polar cap patches are related to dayside auroral structures like poleward moving auroral form (PMAF) (Lorentzen et al., 2010; Nishimura et al., 2014; Zhang et al., 2010) and throat aurora (Zhang et al., 2023). Our auroral arc was accompanied by electron density enhancement and soft‐electron precipitation (Michell et al., 2008), but the relationships between polar cap patches and auroral arcs in the polar cap needs to be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…The cold patches are related to solar activity and found in the central polar cap (D. Zhang et al, 2021Zhang et al, , 2022. The hot patches are found close to the auroral oval, associated with strong auroral emissions, ion upflows, and flow shears (e.g., Lorentzen et al, 2010;Ma et al, 2023;Nishimura et al, 2014;Zhang et al, 2023). The electron temperature of a hot patch may decrease to the same level as the ion temperature when the particle precipitation decreases, that is, it becomes a cold patch (Ma et al, 2023), which was obtained by analyzing two different patch events, rather than a complete evolution process of a patch.…”
Section: Plain Language Summarymentioning
confidence: 99%